Some fixed point results for dualistic rational contractions - Muhammad Nazam; Muhammad Arshad; Mujahid Abbas (Applied General Topology, 2016)
In this paper, we introduce a new contraction called dualistic contraction of rational type and obtain some fixed point results. These results generalize various comparable results appeared in the literature. We provide an example to show the superiority of our results over corresponding fixed point results proved in metric spaces.